Advances in Nanostructured Cellulose-based Biomaterials. (2017) - Carreño, Neftali L V; Barbosa, Ananda M; Noremberg, Bruno S; Salas, Mabel M. S; Fernandes, Susana C M; Labidi, Jalel
No abstract available